Development of Innovative Technologies for the Synthesis of Materials for Sensing and Environmental Applications - BRESSI, Viviana (2023)
This doctoral research focuses on the comprehensive conversion of waste materials and biomasses through sustainable approaches, yielding carbon-based materials that exhibit advantageous properties and captivating capabilities for catalytic processes and detection of environmental pollutants. Humanity progression has consistently been intertwined with scientific and technological advancements. However, this route has occurred over the course of centuries, often at the detriment of the Earth’s resources, leading to climate change, biodiversity loss, stratospheric ozone depletion, disorders in nitrogen and phosphorus cycles, ocean acidification, environmental pollution, and the dispersion of hazardous gases in the atmosphere. In recent years, the research community became aware of this harsh reality, by aligning itself with the 12 principles of Green Chemistry and the 17 Sustainable Development Goals (SDGs) outlined in the 2030 agenda by the United Nations. On this account, the objective of this research endeavour was to harness the potential of biomass sources, which could pose threats to ecosystems and, directly or indirectly, to human safety. This was accomplished by transforming them into valuable carbonaceous materials through the development of straightforward and environmentally compatible processes. Moreover, according with Green Chemistry’s principles, emphasizing the utilization of renewable raw materials and waste reduction, along with SDGs commitment to mitigating the impacts of climate change and promotion of aquatic life, and its inhabitants’ well-being, these innovative green materials were harnessed as adsorbents for the removal of hazardous organic pollutants, as supports for catalytic processes and as selective and simultaneous sensor detection systems for heavy metal ions. These advancements have opened the doors to promising outcomes, suggesting a significant stride towards establishing a fully sustainable scientific community.